Maqashid Sharia Analysis of Change From Customers for Donation: a Case Study in Fajar Toserba, Jalaksana District - Alfan Syafi'i; Ega Kusuma Dewi (Jurnal Ekonomi dan Perbankan Syariah, 2021)
The Qur'an and Islamic legal literature do not mention the word Islamic law as one of the terms in the Qur'an is the word syarî'ah, fiqh, Allah's law, and the same root with it. The term Islamic law is a translation of Islamic Law in western literature. If traced to its roots, then the meaning of Islamic law is "control or bridle of the horse", what is meant here is that in essence the law exists to regulate people who are subject to the law itself. Other meanings derived from the root word hakama include preventing injustice, preventing tyranny, preventing persecution, and rejecting other mafsadat. The research on Maqashid Syariah analysis of the ask foral of change for donations (a case study in Fajar Toserba, Jalaksana District) aims to understand how the practice of asking for change for donations is, how the distribution of these donations when they have been collected, and how Muqashid Syariah analyzes the practice of asking for change for donations. donation. This study uses a descriptive qualitative method because it describes the data in the form of a written description. Types and sources of data in this study using primary and secondary data. Data collection techniques through interviews and observations. The results of this study are on the ask foral of change for donations at Fajar Toserba Jalaksana when buying and selling transactions. As for the practice, when buying and selling at Fajar occurs, if there is odd nominal money, it is directly distributed to the social fund in the payment receipt. Maqashid Sharia analysis on this matter can be concluded that the five main points or al-mabaadi 'al-khamsyah have been fulfilled. customers for change for donations and distributing the donation money have fulfilled the purpose of Islamic law itself, namely Maqashi Syariah. Although there are elements that should not be done, in this case, the benefits are greater.